Going concern and audit opinion: studies on banking companies on the Indonesian stock exchange for the period 2003-2008 - Handoyo estdwinanto (Indonesia Auditing Research Journal, 2022)
The primary aim of this study is to investigate the usefulness of the bankruptcy prediction model for assessing going concern to help the auditor issue better going concern opinion. The model bankruptcy prediction firm for banking industry characteristic Model bankruptcy prediction proxed by three general financial ratios; capital ratios, risk financial ratios, and Z-score Altman ratio in Indonesia have been taken from the previous research of Bank Indonesia. The samples of this study are public commercial banks listed in JSX (Jakarta Stock Exchange) for the year 2003 to 2008. There are 114 samples which are collected by pooled data method and the samples are selected with purposive sampling method. Binary logistic regression SPSS version 15 tool used as aim for analyzing. The results show that capital ratios are effective for assessing going concern to predict the issuance of going concern opinion. Both univariate analysis and multivariate analysis show that 5 variables are significant. For the rest, financial risk ratios have 3 variables are significant and Z score Altman ratios have 1 variables are significant.